Defining Duty in the Civil War : Personal Choice, Popular Culture, and the Union Home Front - Gallman, J. Matthew (James Matthew) (Book collections on Project MUSE., 2015)
Examining the breadth of Northern popular culture, J. Matthew Gallman offers a dramatic reconsideration of how the Union's civilians understood the meaning of duty and citizenship in wartime. Gallman shows how thousands of authors, artists, and readers together created a new set of rules for navigating life in a nation at war.